Effect of oIntermittent Drainage and Fertilization on pH, Eh, Fe, and Mn at New Paddy Soil in Ultisols of Bandar Abung (Lampung) and Tapin (South Kalimantan) - Dedi Nursyamsi; Mangku E Suryadi (Jurnal Ilmu Tanah dan Lingkungan, 2000)
To study the effect of intermittent drainage and fertilization on new paddy soil of pH, Eh, Fe,and Mn, laboratory experiment was conducted using Ultisol of Bandar Abung, Larnpung and Tapin,South Kalimantan. Experiment was carried out using Completely Randomized Block Design with 5treatments and 3 replications. The treatments consist of control, organic matter (rice straw) 5,000kg/ha, KzSOI 100 kgha, dolomite SO0 k p a and intermittent drainage. In the drainage treatment thesoil was drained on the 3d, 5th, 7th, 12 , 14'~a~nd 1 6 w~e ek for 7 days respectively. The resultsshowed that intermittent drainage did not affed soil pH, increased soil Eh, decreased soil and water Fe II, and concentration of Mn II in flooded water in both Ultisols of Bandar Abung and Tapin. Organic matter did not affed soil pH, decreased soil Eh, increased soil and water Fe II and concentrattion of Mn II in flooded water in both UAisols of Bandar Abung and Tapin. The higher the soil Fe dithionit andDTPA in the soils caused higher risk in Fe toxicity.